The development of vocational maturity in pupils by means of a classroom career education program - Laubscher, Jacobus Willem Theron (Not Specified, 2024)
A career education program, focusing on self-awareness, was written with the aim of developing the vocational maturity of pupils. The program was taught by guidance teachers to two Standard Ten classes in the same boy's school (N = 48) and to one Standard Nine class in a co-educational school (N = 27). A pre-post test design, with three control classes in the same standards and schools, was used. It was hypothesized that : (1) vocational maturity and (2) job certainty would improve; (3) intelligence and (4) personality are related to vocational maturity, and are also related to a change in vocational maturity (3a, 4a). Using a variety of measures, including the Career Maturity Inventory and the H.S.P.Q., significant results were obtained only for Hypothesis (1), (for one Standard Ten class only) and for Hypotheses (2) and (4), (for both Standard Ten classes only). Further analyses revealed that vocational maturity had a positive relationship with job certainty and a negative relationship with parental aspiration. It was concluded that the program satisfied the aim and that personality development should become an important aspect of career education.